Increased striatal functional connectivity is associated with improved smoking cessation outcomes: A preliminary study. (21st May 2020) - Wang, Chao; Huang, Peiyu; Shen, Zhujing; Qian, Wei; Wang, Shuyue; Jiaerken, Yeerfan; Luo, Xiao; Li, Kaicheng; Zeng, Qingze; Zhou, Cheng; Yang, Yihong; Zhang, Minming
Abstract: The striatum is the critical area of reward processing and has been repeatedly linked to nicotine addiction. However, it remains unclear whether different smoking cessation outcomes (relapse or not) are associated with different functional connectivity changes of the striatum during smoking cessation treatment. A total of 30 treatment‐seeking smokers were recruited in the study and underwent magnetic resonance imaging (MRI) scans immediately before and after a 12‐week treatment with varenicline. After the 12‐week treatment with varenicline, 14 subjects relapsed to smoking (relapsers), whereas 16 not relapsed (nonrelapsers). Changes in resting‐state functional connectivity (rsFC) across groups and visits were assessed using repeated measures analysis of covariance (ANCOVA). Significant interaction effects were detected: (1) between left nucleus accumbens (NAc) and left orbitofrontal cortex (OFC), insula, inferior frontal gyrus (IFG), and bilateral precuneus; (2) between right NAc and left insula, IFG, and bilateral dorsolateral prefrontal cortex (DLPFC); and (3) between bilateral putamen and left precuneus. Post hoc region‐of‐interest analyses in brain areas showing interaction effects indicated significantly decreased rsFC after treatment compared with before treatment in relapsers but opposite longitudinal changes in nonrelapers. These novel findings suggest that increased striatal rsFC is associated with improved smoking cessation outcomes. These striatal functional circuits may serve as potential therapeutic targets for more efficacious treatment of nicotine addiction. Abstract : Increased functional connectivity of the striatum is associated with improved smoking cessation outcomes.